Practical Application of In-door Tested Scaled Models on Real Building structures - Irshad Ullah; MNR Baharom; H. Ahmad; H.M. Luqman; Zainab Zainal (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Lightning indoor testing got a very low attention of the researchers. Although lightning is impossible to create inside the laboratory however it can be presented using high voltage impulse. High voltage impulse was generated in this paper which presents the actual lightning. Selected building structures were tested under the high voltage condition. This idea was implemented practically by applying it on different real building structures. Different building with different roof tops were observed practically and it was found that this research work has a good agreement of the lightning strike points observe during the indoor activities in high voltage lab and out door activity during the field study.